2015
DOI: 10.1074/jbc.m115.644906
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Plasmodium vivax Tryptophan-rich Antigen PvTRAg38 with Band 3 on Human Erythrocyte Surface Facilitates Parasite Growth

Abstract: Background: Plasmodium tryptophan-rich antigens are involved in host-parasite interaction. Results: Plasmodium vivax tryptophan-rich antigen PvTRAg38 interacts with three exofacial loops of Band 3 through its peptide domain KWVQWKNDKIRSWLSSEW to facilitate parasite growth. Conclusion: A novel receptor-ligand interaction between host and parasite has been defined. Significance:The study will help in understanding the host-parasite interaction and development of therapeutics for vivax malaria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
53
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(64 citation statements)
references
References 40 publications
(56 reference statements)
3
53
1
2
Order By: Relevance
“…Basigin Interacts with PvTRAg38 through its P 2 RegionPvTRAg38 interacts with erythrocytes through two peptide regions, P 2 and P 4 at amino acid positions 161-178 and 197-214, respectively (19). Further studies revealed that last six amino acids of this P 4 peptide were not involved in erythrocyte binding, but multiple residues of the remaining 12 amino acid peptides interact with its erythrocyte receptor (20).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Basigin Interacts with PvTRAg38 through its P 2 RegionPvTRAg38 interacts with erythrocytes through two peptide regions, P 2 and P 4 at amino acid positions 161-178 and 197-214, respectively (19). Further studies revealed that last six amino acids of this P 4 peptide were not involved in erythrocyte binding, but multiple residues of the remaining 12 amino acid peptides interact with its erythrocyte receptor (20).…”
Section: Resultsmentioning
confidence: 99%
“…Among these three erythrocyte proteins, band 3 has already been confirmed as one of the erythrocyte receptors for this parasite ligand (19). Therefore, we planned to study direct interaction between PvTRAg38 and each of the other two erythrocyte proteins.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations